Gastroprotective effects and antioxidant activities of paederia pilifera hook.f. root extract - Kanokporn Saenphet (2018)
© 2014, Chiang Mai University. All rights reserved. Gastric ulcer is a type of gastrointestinal diseases, which affects people all over the world. Modern gastric ulcer drugs have various severe side effects and show less efficacy. Thus, more effective and safer anti-ulcer agents are needed. Reactive oxygen species have important roles in the pathogenesis of various diseases, including gastric ulcers. The gastroprotective effects and the antioxidant activities of Paederia pilifera Hook.f. (Rubiaceae) root extract were examined on ethanol-induced gastric ulcers in rats. The effects of the plant extract and omeprazole on ulcer index, percentage inhibition, antioxidant activities and lipid peroxidation were evaluated. Antioxidant properties of the plant in vitro were also determined. Root extract of P. pilifera exhibited high total phenolic and ascorbic acid contents and showed free radical scavenging activities. Pretreatment with P. pilifera extract at all doses (250, 500, 750 mg/kg BW) and omeprazole exhibited a significant reduction in gastric mucosal lesions. The percentage inhibition in the rats treated with the extract was dose dependent. Pretreatment with P. pilifera extract and omeprazole showed a significant decrease in lipid peroxidation and an increase in the activities of catalase (CAT) and superoxide dismutase (SOD) enzymes and glutathione (GSH) levels. The cyto-protective and antioxidant properties of the extract found in this study could be due to the presence of the bioactive compounds in extract.